1997
DOI: 10.1128/jvi.71.12.9508-9514.1997
|View full text |Cite
|
Sign up to set email alerts
|

The extent of early viral replication is a critical determinant of the natural history of simian immunodeficiency virus infection

Abstract: Different patterns of viral replication correlate with the natural history of disease progression in humans and macaques infected with human immunodeficiency virus type 1 (HIV-1) and simian immunodeficiency virus (SIV), respectively. However, the viral and host factors influencing these patterns of viral replication in vivo are poorly understood. We intensively studied viral replication in macaques receiving identical inocula of SIV. Marked differences in viral replication patterns were apparent within the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(81 citation statements)
references
References 63 publications
6
72
2
1
Order By: Relevance
“…These observations highlight the urgency of initiating ART as early as possible when acute infection is diagnosed. The VL kinetics observed in our studies are similar to the earlier acute simian immunodeficiency virus and HIV studies, which showed that VL levels and patterns were influenced by the available target cells and host immune responses [14][15][16]. The levels of viremia during the first week of acute infection and at set-point were highly correlated; the latter was a critical determinant for disease progression [1,15].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These observations highlight the urgency of initiating ART as early as possible when acute infection is diagnosed. The VL kinetics observed in our studies are similar to the earlier acute simian immunodeficiency virus and HIV studies, which showed that VL levels and patterns were influenced by the available target cells and host immune responses [14][15][16]. The levels of viremia during the first week of acute infection and at set-point were highly correlated; the latter was a critical determinant for disease progression [1,15].…”
Section: Discussionsupporting
confidence: 85%
“…The VL kinetics observed in our studies are similar to the earlier acute simian immunodeficiency virus and HIV studies, which showed that VL levels and patterns were influenced by the available target cells and host immune responses [14][15][16]. The levels of viremia during the first week of acute infection and at set-point were highly correlated; the latter was a critical determinant for disease progression [1,15]. The decline from peak viremia was due mainly to the depletion of productively infected cells [14][15][16].…”
Section: Discussionsupporting
confidence: 85%
“…Such findings have lead to the suggestion that CTL do not contribute significantly to virus control in these cases. This is in contrast to findings that link the decline of virus load in acute HIV-1 infection to the rise of CTL responses, and that correlate more vigorous CTL responses to lower setpoint virus loads and slower disease progression (Phillips et al 1991;Koenig et al 1995;Borrow et al 1997;Goulder et al 1997a;Lifson et al 1997). The evolutionary dynamics of CTL escape mutants appear to be more complex than those of drug-resistant virus strains, which tend to appear readily under the appropriate selection pressures.…”
Section: Discussioncontrasting
confidence: 63%
“…At the beginning of the infection, before the immune response is mounted (a' ≈ 0), and after the initial peak of viral load, viruses and infected and uninfected cells reach a stable equilibrium termed viral set point (Figure 3). While monitoring viral load of SIV in infected macaques, a correlation between the viral load at initial stages of the infection and the viral set point was observed [152,153]. One can demonstrate that the equilibrium abundance of viruses, v*, and the logarithm of the virus load during the exponential growth phase, follow the linear relationship…”
Section: Virus Dynamics and Therapeutic Vaccinesmentioning
confidence: 93%